Faktor-faktor yang Mempengaruhi Volume Perdagangan Saham Menggunakan Multivariate Adaptive Regression Splines - Otok, Bambang Widjanarko; Guritno, Suryo; Subanar, . (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
This research aims to know influence the Composite Index on price Share (IHSG), Right Issue, Dollar Rate and interest rate storey level of Singapore International Bonk Offered Rate (SIBOR) to on trading volume stock in Effect Exchange Surabaya. This matter ii- oftentimes studied with regression analysis, and at this article introduce approach which relative n